Leadership in Action : Getting Culture - Imbuing Your Organization with Coaching Behavior - Hart, Wayne (Center for Creative Leadership, 2005)
Organizations are finding that creating a coaching culture, in which everyone thinks in terms of developing and improving the performance of others as an aspect of doing his or her own job, generates synergy.